Determinants of iatrogenic femoral pseudoaneurysm after cardiac catheterization or percutaneous coronary intervention via the femoral artery - Fatih Erol; Sakir Arslan; Isa Oner Yuksel; Cagin Mustafa Ureyen; Serkan Serdar; Sinan Inci; Huseyin Senocak (KARE Publishing, 2015)
OBJECTIVE: This study aimed to define the prevalence and predictors for pseudoaneurysm after coronary angiography, cardiac catheterization and percutaneous coronary interventions (PCIs) performed via the femoral artery. METHODS: The study included 8469 patients enrolled between January 2007 and December 2009 on whom cardiac catheterization, coronary and/or peripheral angiography and PCIs via the femoral artery were performed. All data, including clinical characteristics and complications, were obtained retrospectively from patient chart records. RESULTS: Pseudoaneurysm was detected in 65 (0.76%) patients. Pseudoaneurysm was ascertained more frequently in patients with a history of coronary artery disease (0.9% vs. 0.4%; p=0.012), in females than in males (1.4% vs. 0.5%; p<0.001), in patients older than 65 years (1.2% vs. 0.6%; p=0.002), in patients with a history of femoral artery intervention (1.2% vs. 0.6%; p=0.01), in hypertensives than in normotensives (1.3% vs. 0.5%; p<0.001), in patients taking low molecular weight heparin (1.0% vs. 0.2%; p<0.001), in patients taking clopidogrel (1.0% vs. 0.4%; p=0.007), and in patients with chronic renal disease (3.8% vs. 0.7%; p<0.001). There was no statistically significant trend (1.2% vs. 0.7%; p=0.053) towards more pseudoaneurysm formation in emergent interventions than in elective procedures. CONCLUSION: Patients with a higher risk of pseudoaneurysm development following intervention via the femoral artery should be specified and extra attention given during the intervention. These patients should be informed of the increased risk of this complication and its results, and should be under close follow-up concerning development of iatrogenic femoral pseudoaneurysm.